1995
DOI: 10.1093/tropej/41.6.374
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Low Birth Weight in an Industrial Area in India

Abstract: In an industrial hospital in India, a 23 per cent prevalence of low birth weight (LBW) was detected, of which 76 per cent were full term small for date (SFD) babies. Hypertensive disorders of pregnancy (HDP) comprised the single most common obstetrical problem associated with term SFD births (31 per cent). Age, parity, booking and socio-economic status were all found to contribute to LBW. Babies weighing between 2.25 and 2.5 kg did not show any significant difference in mortality and morbidity as compared to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This method of comparison, wherein the measures of birthweight in two groups are compared on their associations with other variables, with prior knowledge as to what these associations look like, is called “criterion related validation”[34]. Specifically, we found, in both groups, socioeconomic advantages to be associated with lower likelihood of low birthweight, consistent with previous studies[19], [21], [31]. We also found associations of birthweight and low birthweight with later growth failure that were consistent with those of earlier research in both groups[35].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This method of comparison, wherein the measures of birthweight in two groups are compared on their associations with other variables, with prior knowledge as to what these associations look like, is called “criterion related validation”[34]. Specifically, we found, in both groups, socioeconomic advantages to be associated with lower likelihood of low birthweight, consistent with previous studies[19], [21], [31]. We also found associations of birthweight and low birthweight with later growth failure that were consistent with those of earlier research in both groups[35].…”
Section: Discussionsupporting
confidence: 86%
“…While there are multiple studies of birthweight in India[15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], some of them well designed community-based cohorts[30], [31], [32], [33], they remain local studies. The NFHS-3 is the only source that provides data from a sample of individuals across the country and includes data from a majority of sociodemographic groups of the Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from urban population of Bhilai reports LBW proportion of 23% which is rather high for urban population [11].…”
Section: Discussionmentioning
confidence: 92%
“…A community based study in rural areas of West Bengal, urban re-settlement of Delhi and Pune documented the magnitude of LBW as 31.3%, 39.1% and 29% respectively [6][7][8] . National Neonatal-Perinatal Database (NNPD) from secondary & tertiary care network (n=15) reported LBW as 31.3% (2002-03) 9 while isolated Indian hospital based studies at Orissa, Shimla, Bhilai and Amritsar, reported LBW as 39.8%, 27.8%, 23% and 16.3%, respectively 10,11,12,13 .…”
Section: Discussionmentioning
confidence: 99%